Spatial distribution of pediatric cancer patients using Geographic Information System (GIS) across the Philippines - Myra Dela P. Oruga; Primo G. Garcia; Loyda A. Cajucom; Rita C. Ramos; Queenie R. Ridulme; Ronaldo De Jesus; Bryan Alcazar; Ma Joanna Vinas; Raymund K. Manago; Raya K. Fuentes (Jurnal Keperawatan Padjadjaran, 2024)
Background: Every year, many children around the world get cancer, and this is a severe health problem. The Philippines is one such country where childhood cancer is a leading cause of death. This study uses unique maps (Geographic Information Systems or GIS) to examine these young cancer patients' locations. By doing this, we hope to find areas with more cases and see if children in those areas have easy access to the medical care they need. Methods: Methods involved primary and secondary data collection, including surveys and hospital records, with geospatial data analyzed using QGIS 3.4 Madeira. The study focuses on four Department of Health (DOH) tertiary hospitals: Philippine Children Medical Center (PCMC), Bicol Regional Training and Training Hospital (BRTTH), Southern Philippines Medical Center (SPMC), and Vicente Sotto Memorial Medical Center (VMMC) Participants from significant regions contributed to the study. Results: Results indicate that cancer centers, notably the primary children’s hospital, cater to patients from far-reaching areas, causing them to consult distant hospitals despite accessible alternatives. Nearly all (around 92.5%) patients seek care at specialized hospitals, even though only a small proportion (roughly 12.3%) live close to such facilities. Instead, 37.3% reported the closest health facility (within 10 kilometers) is a secondary government hospital, increasing the burden on patients with additional travel and non-medical costs. Conclusions: The study concludes that pediatric cancer patients face challenges accessing healthcare facilities, necessitating alternative methods like telemedicine and mobile clinics. The findings underscore the need for improved healthcare infrastructure and human resources to address the burdens faced by these patients.